Design of novel tripyridinophane-based Eu(iii) complexes as efficient luminescent labels for bioassay applications. Issue 1 (8th December 2021) - Leygue, Nadine; Picard, Claude; Faure, Pamela; Bourrier, Emmanuel; Lamarque, Laurent; Zwier, Jurriaan M.; Galaup, Chantal
Abstract : Synthesis, photophysical characterisation, relative stability and evaluation by fluoroimmunoassay of new luminescent europium complexes on a tripyridinophane-based platform are described. Abstract : In this work, the development of highly luminescent europium(iii ) complexes in water solution is reported, including their syntheses, analyses of their photophysical properties and applications in bioassays. Three Eu(iii ) complexes are derived from new ligands based on a tripyridinophane platform. There are four distinct sections in the structure of these ligands: an 18-membered polyaminocarboxylic macrocycle to bind efficiently lanthanide ions in aqueous solutions, three chromophoric subunits (4-(phenylethynyl)pyridine moieties) to effectively sensitize the emission of the metal, two peripheral moieties to solubilise the complex in aqueous media (sulfonate, sulfobetaine or glucose groups) and a free NH2 group available for grafting or bioconjugation. In our synthetic procedure, a pivotal macrocyclic platform is obtained with a high yield in the crucial macrocyclization step due to a metal template ion effect (74% yield). In Tris aqueous buffer (pH 7.4), the Eu(iii ) complexes show a maximum excitation wavelength at 320 nm, a suitable overall quantum yield (14%), a relatively long lifetime (0.80 ms) and a one-photon brightness in the range of 10 000 M −1 cm −1 . Importantly, these photophysical properties are retained at dilute concentrations, even in the presence of a very large excess of potentially competing species, such as EDTA or Mg 2+ ions. Furthermore, we report the bioconjugation of a Eu(iii ) complex labelled by an N -hydroxysuccinimide ester reactive group with an antibody (anti-glutathione- S -transferase) and the successful application of the corresponding antibody conjugate in the detection of GST-biotin in a fluoroimmunoassay. These new complexes provide a solution for high sensitivity in Homogeneous Time-Resolved Fluorescence (HTRF®) bioassays.